Management of paravalvular regurgitation after Edwards SAPIEN transcatheter aortic valve replacement: Management of paravalvular regurgitation after TAVR. Issue 2 (11th April 2013) - Martinez, Claudia A.; Singh, Vikas; O'Neill, Brian P.; Alfonso, Carlos E.; Bilsker, Martin S.; Martinez Clark, Pedro; Williams, Donald; Cohen, Mauricio G.; Heldman, Alan W.; O'Neill, William W.
<x xml:space="preserve">Abstract</x> Background With the expansion in the use of transcatheter valve therapies for aortic stenosis, the incidence of hemodynamically significant paravalvular regurgitation (PVR) has become a clinical challenge. Methods The study population consisted of those patients with either acute significant PVR immediately post‐Edwards SAPIEN (ES) aortic valve implantation, requiring additional maneuvers during the index transcatheter aortic valve replacement (TAVR) or symptomatic PVR requiring treatment by transcatheter closure at a later date. All the patients were assessed within 24 hrs, 30 days, 3 months, 6 months and 12 months after the procedure. Results A total of 100 consecutive patients underwent ES TAVR (62% with 23 mm and 38% with 26 mm valve), of them 27% (27/100) were identified to have hemodynamically significant PVR requiring additional percutaneous interventions during or after the index procedure. Patient's mean age was 85 ± 12 years and 74% (20/27) were male. The mean Society of Thoracic Surgeon Score was 11.3% (range 4.6–17.6%), 59% had a 23 mm and 41% had a 26 mm ES valve. There was no difference in the occurrence of PVR between a) two valve sizes—23 mm (16/62) vs. 26 mm (11/38) (P = 0.817) and b) the two approaches—transfemoral (15/48) vs. transapical (TA) (12/52) (P = 0.37). A total of 32 procedures were performed on the 27 patients: one patient required four and two required two procedures each. There were 19 repeat ballooning, seven valve in valve and six transcatheter device closure procedures. The approach was retrograde in 66%, antegrade transeptal in 6% and antegrade TA in 28%. The procedural success rate was 90.6%, the total 30‐day, 3 months and 6 months mortality rate was 7.4, 18.5, and 22% respectively. At the time of final analysis a total of 56% (15/27) had completed a 12 month follow‐up. Conclusion The management of PVR in the TAVR era is a technical challenge. We present our experience and propose a management approach. © 2013 Wiley Periodicals, Inc.